Human Values Based on Pancasila Viewed from Islamic Education - Hosaini, Hosaini; Kandiri, Kandiri; Minhaji, Minhaji; Alehirish, Mustafa Hamed Mohamed (Letiges, 2024)
This research aims to internalize Pancasila-based human values according to Islamic views in an Indonesian context, which is a benchmark in upholding Human Rights (HAM) to maintain and preserve the dignity and dignity of humans as creatures with the same rights to equality and justice between creatures. This research uses a qualitative approach through a literature review. The literature review system can obtain data from books, journals and reports of relevant research results. Data is collected by searching several kinds of literature, observations, and documents or texts, which are then narrated. Data analysis is done by simplifying the data into a form that is easy to read and interpret. The results of this research found that the values of Pancasila in the Indonesian context in the Islamic view are recognizing the existence of human dignity, recognizing the existence of humans as the noblest creatures created by God, upholding human values and acting reasonably towards fellow humans as well as being considerate and not be mean to other people. The findings of this research are a benchmark for having openness and empathy towards fellow humans. By respecting and upholding Human Rights (HAM), building equality between people, being fair, establishing fraternal relations throughout the country and providing education to the public, they become humanist individuals with a spirit of patriotism and nationalism towards the nation and state.